The Role of Personal Values and Empathy in a Cooperative Game (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Are the personal values of others a relevant cue when thinking about cooperating, and do values matter more than empathizing with others? To address these questions, the present study presented participants (N = 120) with the details of personal values (social values [e.g., family, friends] or economic values [e.g., phone, bike]) held by fictitious players of a linear public goods game (PGG). In addition, half those tested were induced to empathize with the other players via presenting perspective-taking instructions (empathy induction), and the other half were not. For those that believed they were interacting with real players in a cooperative game (n=70) values did indeed matter. Participants acted more cooperatively in the Social Value condition as compared to the Economic Value condition when there was empathy induction. While empathy induction (perspective-taking instructions) made little difference to levels of cooperation, it did reduce the use of the tit-for-tat strategy in the game. These findings present some challenges to recent work promoting the role of empathy in pro-social behaviors